Speculative Black Feminist Epistemologies of Worldbuilding for XR - Hill, Clareese (Frontiers in Communication, 2024)
Speculative Black Feminist Epistemologies of Worlding Building for XR is a methodology attempting to address space, the production of space, permission of space, the economy of space, and evading the confines of space by activating possible imaginaries in the development of XR (Extended Reality) environments. Through a praxis straddling academic and artist writing, the argument explores an experimental approach to worldbuilding for XR by upending the role of Cartesian coordinates as the default measurement of 3D space. The possibilities afforded XR technologies allow for experimenting with unrestricted navigation of Black women's cartographic movements, which is impossible in real-world geography. The core proposition of the Black Feminist Episteme of Worldbuilding is the praxis of de-mapping. This praxis foregrounds fugitive movements and spaces by utilizing XR worldbuilding affordances as a speculative container for reimagining navigation for identities under conditions of subjugation. Researching and speculating about the affordances of XR is a critical intervention attempting to counter mainstream development and deployment of immersive media technology dedicated to the pedagogical tasks of gaming, militarization, and other real-world training applications. The first move towards the praxis of de-mapping, an arrival, is acknowledging the material composition and operation of XR technology. The second move and the first departure explore intentional disorientation. The third move interrupts the linearity of departures and arrivals to establish mobility as a counter-cartographic methodology by referencing the female protagonists in the work of Octavia E. Butler.